Experimental study on hydrocyclone desanding of high-viscosity oil. (1st June 2023) - Zhang, Shijian; Jing, Jiaqiang; Luo, Min; Qin, Min; Zhang, Feng; Yuan, Liang
Highlights: We developed a hydrocyclone desanding experimental device for high-viscosity oil. We found the range of operating parameters for high-viscosity oil desanding. We found some methods to resist the interference of dissolved gas. Abstract: Crude oil containing sand brings serious safety hazards to the surface gathering system, and wellhead sand removal could basically eliminate the sand threat to the pipelines and equipment. We developed a hydrocyclone desanding experimental device, using high-viscosity industrial white oil to simulate the high-viscosity crude oil on site to carry out the hydrocyclone desanding experiment, and explored the factors such as the oil viscosity, water content and gas injection on the hydrocyclone separation. The range of operating parameters for efficient hydrocyclone desanding of high-viscosity oil was found. The results showed that the hydrocyclone is not suitable for de-sanding of pure oil, but adding water could significantly improve the inefficient desanding state caused by the increase of oil viscosity. And the higher the viscosity of white oil, the more water is needed. Feed stream containing gas would cause a significant increase in pressure drop, which would waste excess pressure energy. Therefore, it is recommended that the dissolved gas should be removed before hydrocyclone desanding on site. Increasing the inlet flow rate, reducing the oil viscosity and increasing the water content could enhance the resistance to the interference of the gas.